Clinical Case of Rare Variant of Inherited Dermatosis: Acrodermatitis Enteropathica - Elena Y. Khorosheva; Kseniya P. Kuzmicheva; Elena B. Khramova; Olga A. Rychkova; Natalya E. Gorokhova; Elena I. Malinina (Вопросы современной педиатрии)
Background. Acrodermatitis enteropathica is the rare form of inherited dermatoses. The disease onset in children is associated with the ablactation and the beginning of cow milk products use, that makes differential diagnosis of acrodermatitis and allergic dermatoses pretty difficult. The caution of specialists to hypozincemia at periorificial dermatitis combined with alopecia and diarrhea in infants will allow to establish correct diagnosis and choose management timely. Clinical Case Description. The clinical case of erosive- desquamative dermatitis combined with alopecia and hypozincemia is presented in this article. Positive dynamics of skin lesion due to administration with zinc sulfate medication is shown. Conclusion. The presence of periorificial dermatitis in the child of any age requires to perform the differential diagnosis for zinc deficiency conditions.